Pengaruh Faktor Sosial Ekonomi Petani Terhadap Tingkat Adopsi Inovasi Pupuk Organik Cair Nitrobacter di Kecamatan Jaten, Kabupaten Karanganyar - Wahyudyanti, Fairuz Hanifah; Anantanyu, Sapja; Widiyanti, Emi (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2023)
Nitrobacter liquid organic fertilizer is expected to be able to restore degraded soil fertility. Innovation regarding nitrobacter liquid organic fertilizer is important to be adopted by the community so that changes in behavior occur in both the aspects of knowledge, attitudes, and skills. The purpose of this study was to analyze the influence of socio-economic factors of farmers on the adoption of nitrobacter liquid organic fertilizer innovations in Jaten District, Karanganyar Regency. Methods of data analysis using multiple linear regression. The research location was determined deliberately in Jaten District, Karanganyar Regency. The sample was determined by means of a census of 40 farmers. At the output of multiple linear regression the results of the F test in this study obtained a value of Sig. equal to 0.000, which means that the independent variables simultaneously have an influence on the level of adoption of innovation by farmers in using nitrobacter liquid organic fertilizer. The results of the coefficient of determination obtained R Square of 0.600 or 60%. These results indicate that the adoption rate of farmers' innovation in using nitrobacter liquid organic fertilizer can be explained by the independent variable of 60%, while the remaining 40% is influenced by other variables not examined in this study.